Diet and habitat use of scoters Melanita in the Western Palearctic - a brief overview. - Fox, A D (Wildfowl, 2013)
If patterns of scoter distribution and abundance are to be understood, there is a need to know upon which prey items these birds feed, how they obtain these prey items and the habitats from which these food items are m ost easily harvested. Dietary studies and descriptions of habitats exploited by C o m m o n and Velvet Scoter in the non-breeding season are reviewed. The existing literature strongly suggests that, outside of the breeding season, these species forage mainly upon marine bivalve mol.